Stressful Life Events and Resilience During the COVID-19 Lockdown Measures in Italy: Association With Mental Health Outcomes and Age - Rossi, Rodolfo; Jannini, Tommaso B.; Socci, Valentina; Pacitti, Francesca; Lorenzo, Giorgio Di (Frontiers in Psychiatry, 2021)
Background: The COVID-19 pandemic, due to its disproportionated higher morbidity and mortality rates in the older age, has been considered to be a "geropandemic". Several studies, however, have found that older age is associated with lower psychological distress in relation to the COVID-19 outbreak and related lockdown measures. Aim: To explore the role of Resilience as a mediator between stressful COVID-19 related life events and depressive and, anxiety symptoms and perceived stress, and to ascertain the role of age as a moderator of the mediator's effect. Methods: An on-line survey was spread through social networks during the first lockdown in Italy. Depressive and anxiety symptoms and perceived stress were measured using the Italian version of the Patient Health Questionnaire-9 (PHQ-9), the Generalized Anxiety Disorder Questionnaire-7 (GAD-7) and the Perceived Stress Scale (PSS). Resilience was measured using the Italian version of the Resilience Scale for Adults (RSA). Stressful COVID-19 related life events were explored using a checklist of events derived from the International Adjustment Disorder Questionnaire (IADQ). After a preliminary panel of linear regressions, mediation was tested using Structural Equation Modelling and inspecting the bootstrapped indirect effects. Afterwards, age was introduced as a mediator of the indirect effect in a moderated mediation analysis. Results: 21334 subjects completed the questionnaire, 17178 (80.52%) were female, 748 (3.5%) were > 60 years old. In the whole sample, the presence of any stressful event was associated with depressive and anxiety symptoms and perceived stress. Resilience mediated the effects of stressful COVID-19-related events on depressive and anxiety symptoms and perceived stress. The moderated mediation analysis revealed that age moderated the mediation effect of Resilience between the presence of a stressful event and the selected outcomes. Conclusion: Taken together, our results show that age moderates the mediating effect of resilience in the relationship between COVID-19-related stressful events and depressive and anxiety symptoms and perceived stress. Older adults' Resilience was less influenced by stressful events, and this could be one of the reasons accounting for the better mental health outcomes observed in the older age.